Endometriosis-Associated Angiogenesis and Anti-angiogenic Therapy for Endometriosis - Chung, Monica S.; Han, Sang Jun (Frontiers in Global Women's Health, 2022)
Endometriosis is a known estrogen-dependent inflammatory disease affecting reproductive-aged women. Common symptoms include pelvic pain, dysmenorrhea, dyspareunia, heavy menstrual bleeding, and infertility. The exact etiology of endometriosis is largely unknown, and, thus, the diagnosis and treatment of endometriosis are challenging. A complex interplay of many molecular mechanisms is thought to aid in the progression of endometriosis, most notably angiogenesis. This mini-review examines our current knowledge of the molecular etiology of endometriosis-associated angiogenesis and discusses anti-angiogenic therapy, in the blockade of endometriosis-associated angiogenesis, as potential non-hormonal therapy for the treatment of endometriosis.